Correction: Large-scale synthesis of ultrafine Fe3C nanoparticles embedded in mesoporous carbon nanosheets for high-rate lithium storage. Issue 16 (31st March 2022) - Yu, Ying; Wang, Xuanli; Zhang, Hongkun; Cao, Zhiqin; Wu, Haoyang; Jia, Baorui; Yang, Jun Jun; Qu, Xuanhui; Qin, Mingli
Abstract : Correction for 'Large-scale synthesis of ultrafine Fe3 C nanoparticles embedded in mesoporous carbon nanosheets for high-rate lithium storage' by Ying Yu et al., RSC Adv., 2022, 12, 6508–6514, DOI: ; 10.1039/d1ra08516f .